Avaliação da sinalização purinérgica em plaquetas e linfócitos de pacientes com anemia falciforme - Castilhos, Lívia Gelain (2016)
Sickle cell anemia (SCA) is a hemoglobinopathy characterized by hemolysis and vaso-occlusions caused by rigidly distorted red blood cells, genetically determined by homozigous hemoglobin S (HbSS). The SCA is associated with inflammatory conditions that may result from pro-adhesive and procoagulant phenotype and lead to the majority of deaths related to vascular occlusions. Extracellular nucleotides such as ATP, ADP, AMP and the adenosine nucleoside are important signaling molecules that are necessary for the maintenance and modulation of inflammatory reactions in the platelets and lymphocytes. They also act effectively in the regulation of vascular response from endothelial damage exerting effects on platelets. The extracellular levels of these nucleotides are physiologically controlled by the action of an enzyme complex formed by E-NTPDase, E-5'nucleotidase and E-ADA. These enzymes are located on the surface of platelets and lymphocytes with the aim of maintaining the normal hemostasis and preventing excessive platelet aggregation, as well as modulating inflammatory response. Thus, the function of this study was to evaluate the inflammatory profile, activity and expression of these ecto-enzymes in lymphocytes and platelets of patients with SCA. The results revealed a decrease in the TNF-α and IL-6 serum levels in SCA patients when compared to normal subject (control). Moreover, there were significant (P<0.05) elevations in E-NTPDase and E-ADA activities in lymphocytes and platelets of SCA patients when compared to the control. The increase on its activity leads to the maintenance of physiological levels of these nucleotides in the extracellular environment, preventing a greater tissue damage and inflammation, and preventing the thrombus formation by the balance of the ATP and ADP metabolism. Furthermore, a significant (P<0.05) decrease in the percentage of platelets expressing CD39 was observed in SCA patients, which may be directly related to the therapy used were these patients. In addition, no significant (P<0.05) differences were observed in the E-5'-nucleotidase enzyme activity and expression in SCA platelets and normal subjects. This study suggests that the decreased pro-inflammatory cytokine levels by use of hydroxyurea may have occurred in order to reduce the pro-inflammatory response and prevent vaso-oclusive crisis. Also, the increased E-NTPDase activity could be a compensatory mechanism associated with the low expression of CD39+ in platelets. Also, the AMP formed may be converted to ADP by the action of adenylate kinase 1 (AK1) and this may be attributed to the altered platelet aggregation in SCA patients. The observed increase in ADA activity in SCA may be linked to the release of adenosine by endothelial cells, since high concentration of adenosine in the extracellular environment is detrimental to SCA. Besides, alteration of these enzymes activities may suggest that the purinergic system could be involved in the thromboregulatory process in SCA patients. We therefore conclude that the cytokine profile was modified and the extracellular regulation of nucleotides in response to hypoxia and inflammation by ecto-enzymes in SCA patients on chemotherapy.